2022
DOI: 10.1007/s11926-022-01075-5
|View full text |Cite
|
Sign up to set email alerts
|

Future of Low-Dose Computed Tomography and Dual-Energy Computed Tomography in Axial Spondyloarthritis

Abstract: Purpose of Review Recent technical advances in computed tomography (CT) such as low-dose CT and dual-energy techniques open new applications for this imaging modality in clinical practice and for research purposes. This article will discuss the latest innovations and give a perspective on future developments. Recent Findings Low-dose CT has increasingly been used for assessing structural changes at the sacroiliac joints and the spine. It has developed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Another imaging modality that is increasingly utilized for adult patients with suspected or confirmed sacroiliitis is low-dose CT [38]. The advantage of this imaging modality is that the radiation dose is comparable to an x-ray and it shows the bony changes/damage to the joint(s) in much greater detail.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another imaging modality that is increasingly utilized for adult patients with suspected or confirmed sacroiliitis is low-dose CT [38]. The advantage of this imaging modality is that the radiation dose is comparable to an x-ray and it shows the bony changes/damage to the joint(s) in much greater detail.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recent technical advances significantly reduce radiation exposure, thus allowing more frequent use of this technique in the rather young patient population with axSpA [57,70]. However, standard CT techniques are not sensitive to active inflammation, ▶ Fig.…”
Section: Ctmentioning
confidence: 99%
“…No bone marrow edema is seen in the STIR sequence. and dual-energy CT or comparable techniques are neither well investigated, nor can they be performed with similarly low doses [57]. In clinical practice, CT has been mostly reserved for patients with equivocal MRI findings.…”
Section: Ctmentioning
confidence: 99%
“…This capability is preserved in ldCT of the SIJs, where, because of the high contrast of cortical bone compared with other structures, radiation dose reduction does not compromise image readability (Fig. 3) [39]. Studies have reported ldCT to be more sensitive for detection of erosions or sclerosis than plain radiography and to be highly specific for axSpA while maintaining high inter-reader reliability [19 ▪ ,21 ▪▪ ].…”
Section: Computed Tomography Of the Sacroiliac Joints: A Potential Re...mentioning
confidence: 99%